Mapping the Pains of Neo-Colonialism: A Critical Elaboration of Southern Criminology. (17th May 2021) - Ciocchini, Pablo; Greener, Joe
Abstract: Recent appeals to decolonize criminology argue for a radical reorientation of the subject towards Global South relevant research agendas, theories and scholars. This paper begins by problematizing the current theoretical tendencies in Southern criminology's view of coloniality and the vision for decolonization. First, Southern criminology has not directly engaged in investigating 'empire' in its current form; second, decolonization is viewed as primarily epistemological (transforming systems of knowledge production is seen as the central mode for decolonization); and, third, there is a tendency to reify Southern institutional responses to crime as preferable to Northern crime control. Launching from this critique, we argue that a successful Southern criminology should take seriously the continuing importance of structures of neo-colonialization: the Global system of accumulation founded on various matrixes of inequality, facilitating dispossession, appropriation and exploitation. We develop three criminological analyses of contemporary neo-colonization in Global South contexts: state-corporate 'regimes of permission', political economies of gender violence and racialization through criminalization regimes.